Debt affordability in developed and emerging market economies: The role of fiscal rules - Oscar M. Valencia; José Eduardo Gómez González; Gustavo A. Sánchez (Inter-American Development Bank (IDB), 2022)
This paper studies the effect of fiscal rules on debt affordability in a large set of developed and emerging market economies, using a panel data model which allows the inclusion of weakly exogenous regressors, and which deals appropriately with cross-sectional dependence. The results show a positive and significant effect of fiscal rule implementation on public debt affordability which is robust to various model specifications. The effect is stronger for emerging market economies which benefit from the implementation of any fiscal rule. In contrast, developed countries benefit only from high-quality fiscal rules. The findings have important policy implications for fiscal management, especially in emerging market economies.
Keywords: C33; F34; G15; 330; cross-sectional dependence; debt affordability; emergingmarket economies; fiscal rules; weakly exogenous regressors